ORGANISASI MASSA DAN ALIRAN BARU DALAM PERSPEKTIF AL-QUR'AN - Rohmansyah, Rohmansyah (Al-MAJAALIS, 2017)
Indonesia is a country that is loaded with compounds with the pattern of thought to give birth to a variety of religious organizations and the emergence of new flow that starts from the belief that sometimes cause conflict. This paper aims to explore and analyse the principle of mass organization and the new flow in the Qur'an. This paper uses a contextual approach with descriptive analysis method in understanding the Quran about the mass organization and flow. Research results showed the six principles of the Organization, namely staple Istiqamah, al-Mas'uliyah wa al-Amanah, al-Ghardh al-Wadhih, al-Tawassuth, al-Imam, and al-Khudhu ' wa al-Tha'ah. The flow of so-called "firqah" tends to be interpreted as a negative flow (flow left) again went astray due to a pattern of understanding based on the confidence and trust of its own apart from the Qur'an and al-Sunnah. Keywords: mass organization, the flow of new subject matter, the principle of the organization. Abstrak: Indonesia adalah negara majemuk yang sarat dengan corak pemikiran hingga melahirkan berbagai organisasi keagamaan dan bermunculannya aliran baru yang berawal dari kepercayaan yang kadang menimbulkan konflik. Tulisan ini bertujuan untuk menggali dan menganalisis prinsip organisasi massa dan aliran baru dalam al-Qur'an. Tulisan ini menggunakan pendekatan kontekstual dengan metode deskriptif-analisis dalam memahami al-Quran tentang organisasi massa dan aliran baru. Hasil penelitian menunjukan enam prinsip pokok organisasi, yaitu Istiqamah, al-Mas'uliyah wa al-Amanah, al-Ghardh al-Wadhih, al-Tawassuth, al-Imam, dan al-Khudhu' wa al-Tha'ah. Aliran disebut firqah' yang cenderung diartikan sebagai aliran negatif (aliran kiri) lagi sesat disebabkan pola pemahamannya yang didasarkan pada keyakinan dan kepercayaan sendiri selain al-Qur'an dan al-Sunnah.